2011
DOI: 10.1152/ajpheart.00597.2010
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent vasorelaxation to the AMPK activator AICAR is enhanced in aorta from hypertensive rats and is NO and EDCF dependent

Abstract: Ford RJ, Rush JW. Endothelium-dependent vasorelaxation to the AMPK activator AICAR is enhanced in aorta from hypertensive rats and is NO and EDCF dependent. Am J Physiol Heart Circ Physiol 300: H64 -H75, 2011. First published October 22, 2010 doi:10.1152/ajpheart.00597.2010.-Activation of AMP-activated protein kinase (AMPK) induces vasorelaxation in arteries from healthy animals, but the mechanisms coordinating this effect are unclear and the integrity of this response has not been investigated in dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 59 publications
(100 reference statements)
5
62
3
Order By: Relevance
“…Phosphatidyl-inositol-3-kinase (PI3K) and AMPK are 2 upstream modulators of NO release, which can act independently on their target. 19,20 We found that Compound C, an AMPK inhibitor, significantly blunted the vascular activity of resveratrol ( Figure 1C). In contrast, exposure to LY292002, a PI3K inhibitor, did not modify resveratrol-mediated vasorelaxation ( Figure 1C).…”
Section: Resveratrol Exerts a Vasorelaxant Effect By Modulating The Pmentioning
confidence: 88%
“…Phosphatidyl-inositol-3-kinase (PI3K) and AMPK are 2 upstream modulators of NO release, which can act independently on their target. 19,20 We found that Compound C, an AMPK inhibitor, significantly blunted the vascular activity of resveratrol ( Figure 1C). In contrast, exposure to LY292002, a PI3K inhibitor, did not modify resveratrol-mediated vasorelaxation ( Figure 1C).…”
Section: Resveratrol Exerts a Vasorelaxant Effect By Modulating The Pmentioning
confidence: 88%
“…21 AMPK activation causes the NO-mediated relaxation in the spontaneously hypertensive rats. [25][26][27][28] AMPK, at the same time, causes the endothelium independent vascular smooth muscle relaxation in the aort preparations of the Mouse. 27 …”
Section: Adenosine Monophosphate-activated Protein Kinase Pathwaymentioning
confidence: 93%
“…23 Antidiabetic agents, such as, metformin 24 , thiazolidinediones, glukagon like peptid-1 agonists, dipeptidyl peptidase-4 inhibitors, statins, adiponectin and the leptin hormone increase the AMPK activation. 25,26 Experimentally, 5-aminoimidazole-4-carboxamide ribonucleoside is used for the AMPK activation 24 , whereas the dorsomorphine (compound C) is used for the inhibition.…”
Section: Adenosine Monophosphate-activated Protein Kinase Pathwaymentioning
confidence: 99%
See 2 more Smart Citations